Using macro-financial models to simulate macroeconomic developments during the Covid-19 pandemic: The case of Albania - Lorena Skufi; Adam Gersl (Charles University in Prague, Institute of Economic Studies (IES), 2022)
The recent Covid-19 pandemic has increased the importance of properly forecasting macro-financial developments in turbulent times. Only a limited number of studies focus on how to employ macro-financial models to project key real and financial sector variables under large shocks and unusual assumptions. The aim of this paper is to examine whether a pre-constrained linear model can project the developments seen during the Covid-19 pandemic. We develop a macro-financial model for Albania and, using suitable assumptions, run two types of simulations and compare the results with the outturn. We also take into account the increased forecast risk by constructing uncertainty bands using a quantile regression approach. The results indicate that a linear model is flexible enough to analyse non-linear events and be used in abnormal times, but its precision is lower especially due to the government measures such as repayment moratoria that broke the link between the real and financial sector.
Keywords: E66; C53; C32; 330; macro-financial model; scenario; quantile regression; uncertainty bands; pandemic